DERIVATIVE INSTRUMENTHEDGING ACTIVITY ON COMPANY’S INTERNAL AND EXTERNAL ECONOMIC FLUCTUATIONS - Dian Oktarina (Master of Accounting Universitas Trunojoyo Madura, 2017)
Between 2008-2009, Indonesia had financial crisis which made companies tried hard to stabilize its economy and found solutions or preventive action to resolve the problems of the crisis. Several ways can be applied to resolved these risks, and hedging activity was one solution. Data sampling in this article were taken from automotive industry listed at Indonesian Stock Exchange (BEI) between 2010-2014. The purpose of this study is to determine activity of derivative instruments to hedge the volatility in economic conditions of internal and external company. Internal economy condition is described by financial distress and external economy condition is described by economic exposure. Logistic regression analysis is a tool used in this research. The results indicate that financial distress provides significant negative effect on implementation of hedging activities, while economic exposure does not affect the implementation of hedging activities. Further research can use other sector or using all sector companies listed at the Indonesian Stock Exchange (BEI) and with a longer period of time. However, added some independent variables can affect hedging activities such as interest rates and inflation.